2016
DOI: 10.1051/matecconf/20164806003
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of CDIO Approach in training engineering specialists for the benefit of sustainable development

Abstract: Abstract. Due to the competition and changing needs of the world, universities strive to analyze these needs to timely offer necessary educational programs. One of the newest trends in engineering education is sustainable development. To support the concept and implement it into life it is necessary to train specialists able to promote sustainable development that inevitably leads to the necessity to develop educational programs embracing newest approaches considering up-to-date conditions and requirements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This improves the social responsibility of the subjects of educational activities and is beneficial for University image. Part 2, named «Educational part» includes educational projects (Description and achievements) according to CDIO initiative [3][4][5][6].…”
Section: Portfolio Peculiaritiesmentioning
confidence: 99%
“…This improves the social responsibility of the subjects of educational activities and is beneficial for University image. Part 2, named «Educational part» includes educational projects (Description and achievements) according to CDIO initiative [3][4][5][6].…”
Section: Portfolio Peculiaritiesmentioning
confidence: 99%
“…Daneykin et al 12 proposed that the framework, its standards and syllabus are effective tools to design educational programmes that take into account sustainability. Their study revealed that even world's top universities do not offer programmes that can be taught at various levels of education.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers suggest that the CDIO process prepares engineering graduates to solve more convoluted engineering activities [6]. A formal view to the progress of the project was taken and resulted in a systematic development of the required components which correlates to the CDIO process.…”
Section: Introductionmentioning
confidence: 99%